Pola Kepemimpinan Kepala Sekolah dalam Pembentukan Karakter Kasih Sayang Siswa SMAN 1 Batu - Dedi Eko Riyadi (Mudir : Jurnal Manajemen Pendidikan, 2022)
The researchers attention is that the phenomenon of violence or known as klitih is rife everywhere in Indonesia, both in East Java, Central Java or West Java and in other areas in Indonesia. The forms of violence that occur take various forms, ranging from brawls, rape to what is very ironic is the murder is the background of this research. An example of a case is the death of two students because of the klitih action carried out by a group of students that took place at the Piri I Junior High School in Yogyakarta. This klitih phenomenon is interesting because it is related to character education. For this reason, in order to be more focused and deepen the problem in kama, the author focuses on research related to the efforts of principals and teachers in forming the affectionate character of students at SMAN 1 Batu, through the type of leadership of the principal, exemplary teachers in character building, and efforts to build good character. done by the school. The basic reason why the researcher made SMAN 1 Batu is because this school has implemented and cultivated the character of compassion. So it is very feasible that the results of this research will be used as a reference for other schools, especially schools that have experienced violent phenomena or a phenomenon called klitih. By using a qualitative approach, data were collected through interviews, observation, and documentation. This study found that: first, the principal of SMAN 1 Batu has a paternalistic democratic leadership type. Second, the formation of students affectionate character is formed through the teachers example through discipline, and the application of the 5S concept (greetings, smiles, greetings, politeness, and courtesy). Third, the formation of student character is carried out with conscience, respect, tolerance, empathy, and justice. The character building is carried out together with the school community using an eclectic method.